Application of the Take and Give Learning Method in Learning Physics to Improve Learning Outcomes and Student Activity - Wiwin Ika Hasta Fatmawati (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Teaching and learning activities in the classroom will be effective if there is a reciprocal process between the teacher and students. Learning methods that run in one direction will make it difficult for teachers to measure the level of student understanding of a lesson, especially in exact subjects, Mathematics. In the learning process of physics lessons in class X IL3 SMK Negeri 1 Jatirejo, there is often a passive student condition in teaching and learning activities. Take and Give learning has several steps, starting with making cards that will be distributed to each student. The cards contain one subject matter to be taught. The student's task is to find other cards that contain material other than the material on their card. Then students are asked to study and teach the cards they have to other students. The success indicator of this research is that there are 70% of students who pass the KKM. In the pre-cycle, 63.6% (21 students) completed the KKM. Then, in cycle I, 72.7% (24 students) completed the KKM. Then, in cycle II there were 87.9% (29 students) who completed KKM, while in the activeness of students in each cycle more and more students were included in the classification A (Very Good) and B (Good). On the other hand, the number of students in classification C (sufficient). Meanwhile, students in the classification of D (poor) and E (very poor) scores were not found at the end of the research cycle.